Study on the effects of the shot peening intensity on the microstructure, friction and wear properties of high-strength steel. - Huashen Guan; Junjie Zhang; Xiaoguang Zhang; Guofu Sun; Chenfeng Duan (PLoS ONE)
The microstructure, hardness, residual stress, and friction and wear properties of 25CrNi2MoV steel with different particle diameters during shot peening strengthening were studied. Studies have shown that a grain refinement layer appeared on the surface of the material after shot peening. The shot peening intensity increased with increasing particle diameter; a greater shot peening intensity corresponded to a greater surface hardness of the material, the maximum hardness was 592 HV0.2, and the residual compressive stress on the material surface was 725 MPa. A shot peening finite element model was established to accurately predict the residual stresses in the samples after shot peening. The prediction errors were 1.4-7.9%. The finite element model indicates that the maximum residual stress occurs in the subsurface layer. After shot peening, the wear resistance of the sample significantly improved, and the amount of wear significantly decreased. Therefore, shot peening can significantly improve the mechanical properties and wear resistance of high-strength steel, which increases the service life of parts.